The Serial Engagement Model 17 Years After: From TCR Triggering to Immunotherapy - Valitutti, Salvatore (Frontiers in Immunology, 2012)
More than fifteen years ago the serial engagement model was proposed as an attempt to solve the low affinity/high sensitivity paradox of TCR antigen recognition. Since then, the model has undergone ups and downs marked by the technical and conceptual advancements made in the field of T lymphocyte activation. Here, I describe the development of the model and survey recent literature providing evidence either for or against the idea that serial TCR/pMHC engagement might contribute to T lymphocyte activation. I also discuss how the concept of serial TCR engagement might be useful in the design of immunotherapeautic approaches aimed at potentiating T lymphocyte responses in vivo.